Estudo morfofuncional comparativo de fibroblastos sinoviais de pacientes com artrite reumatóide e de modelo experimental de artrite induzida por colágeno - Rafaela Bicalho Viana Macedo (2013)
The pathophysiology of rheumatoid arthritis (RA) involves the participation of various cells and cytokines. Interleukin 33 (IL-33) is a recently described member of the family of interleukin 1 (IL-1) and its role in the development and perpetuation of the inflammatory response has been demonstrated in several studies in RA patients and in experimental models. In the synovial tissue, synovial fibroblasts (SF) assume behavior in critical inflammatory environment being involved in RA synovitis and structural damage cycle through production of inflammatory cytokines and matrix metalloproteinases (MMPs). Comparative ultrastructural morphology of SF derived from synovial fluid and synovial tissue of patients with RA and experimental model of collagen-induced arthritis (CIA). To study the effect of IL -33 stimulation on these cells for the production of interleukin-6 (IL-6) and MMPs 1 and 3. Evaluate the production of MMPs 1 and 3 after stimulation with tumor necrosis factor alpha (TNF-alpha) and interleukin-1 beta (IL-1 beta). A protocol of cultured fibroblasts from synovium and synovial fluid of RA patients and mice with CIA were established. Human cells were used between the fourth and eighth passages and cells CIA model between 27th and 38th passages. Cells were compared morphologically by transmission (TEM) and scaning electron microscopy (SEM) and scanning. Basal levels of IL-6 were evaluated in murine and human SF. The CIA model SF were stimulated for 18 hours with IL-33 at doses 1, 3, 10, 30 and 100ng/ml TNF-alpha and IL-6 was identified by ELISA. Human SF received stimulation with 10ng/mL IL-33 and IL-6 concentrations were measured after 1, 3, 6, 9, 12 and 24 hours. Also SF were stimulated with human TNF-alpha and IL-1b at doses of 0.5, 1, 5 and 10 ng/ml each alone for 18 hours, and production of MMP 1 and 3 was analyzed by ELISA. Human and murine SF exhibited similar ultrastructural morphology with abundant cytoplasm and presence of lamellated corpuscles. In the CIA model mean basal production of IL-6 was 73,94 (± 4,0) ng/mL and after stimulation with IL -33 increased the production of IL-6 with increasing doses of IL -33. There was no detectable level of basal TNF-alpha or after stimulation with IL -33. In human cells, the concentrations of MMP-1 positively correlated with increased TNF- alpha and IL- 1 beta. The MMP- 1 concentration exceeded the limit of detection method. Human SF from patients with RA and SF from CIA model exhibit similar morphological characteristics, supporting the use of an animal model for the study of disease. The SEM and TEM analysis allowed characterization of SF, since the corpuscles lamellar surfactant-storage organelles are unique synovial fibroblasts inner layer. The behavior of murine SF in response to stimulation with IL -33 confirms the involvement of this cytokine in the inflammatory environment of CIA and has implications for the study and development of therapeutic targets.